High-strength wear-resistant film-coated plate and processing method thereof
By hot-pressing the composite siloxane-modified original wood board and the silanized silica nanotube/ethylene vinyl acetate film, a high-strength wear-resistant coating board is formed, which solves the problem of insufficient strength and wear resistance of the coating board. Higher mechanical properties and wear resistance are achieved.
Patent Information
- Application Number
- CN202411399792.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-24
AI Technical Summary
The film coating plate is not strong enough and has not good wear resistance when used, making it difficult to meet the construction industry's demand for high-strength wear-resistant materials.
Between the two layers of silicohide nano-nanotubes/ethylene-acetate-hypertrophic film was sandwiched by clamping the silicane-alkoxic library. This method includes steps such as thermal pressure composite, cooling and secondary setting, which enhances the mechanical properties and abrasion resistance of the plate.
It significantly improves the static bending strength, surface bonding strength and wear resistance of the film-coated board, solves the problem of insufficient strength and wear resistance of the film-coated board, and meets the construction industry's demand for high-strength wear-resistant materials.
Smart Images

Figure BDA0005074928540000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of film-coated plates, in particular to a high-strength wear-resistant film-coated plate and a processing method thereof. Background Art
[0002] Film-faced plywood refers to a sheet material with a thin film coated on the surface of the base material. The commonly used base material is usually wood fiberboard or wood particleboard, and the membrane material is a polymer film such as polyvinyl chloride and polyolefin. It has excellent wear resistance, waterproofness, corrosion resistance and other properties, and is widely used in the construction industry. At the construction site of the construction industry, compared with wooden formwork, film-faced plywood has higher strength, corrosion resistance, stability and deformation resistance, and can resist the influence of adverse factors on site. When pouring concrete, the use of film-faced plywood can better demould and prevent adhesion, ensuring the quality of concrete construction, and can be reused after simple cleaning, reducing material waste, saving wood resources and reducing the cost of building construction. However, compared with more expensive steel formwork and aluminum alloy formwork, film-faced plywood still has the problem of insufficient strength and poor wear resistance when used. Summary of the invention
[0003] The object of the present invention is to provide a high-strength wear-resistant film-covered plate and a processing method thereof, so as to solve the problem that the film-covered plate has insufficient strength and poor wear resistance.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0005] A method for preparing a high-strength wear-resistant film-covered plate, the preparation method comprising:
[0006] The siloxane-modified log board is sandwiched between two layers of silanized silica nanotube / ethylene-vinyl acetate film for hot pressing and compounding. The hot pressing pressure is 0.8-1.2 MPa, the hot pressing time is 15-25 min, and the hot pressing temperature is 130-150°C. After hot pressing and compounding, it is cooled to room temperature and pressed again for shaping. The secondary shaping pressure is 0.8-1.2 MPa and the secondary shaping time is 3-8 min. After shaping, it is taken out and trimmed to obtain a high-strength wear-resistant coated board.
[0007] As a limitation of the present invention, the preparation method of the siloxane-modified log board is:
[0008] KH-171, neutral silica sol and ethanol are mixed and stirred to obtain a mixed silica ethanol solution. The pH of the mixed silica ethanol solution is adjusted to be alkaline, and the mixture is reacted at 25-30°C for 2-4 hours to obtain a cage silsesquioxane solution. The cage silsesquioxane is sprayed onto the surface of the log board, and the mixture is left to air at 25-30°C for 20-28 hours, and cured at 110-130°C for 1-3 hours to obtain a siloxane-modified log board.
[0009] As a limitation of the present invention, the mass ratio of KH-171, neutral silica sol and ethanol is (4.9-5.1):(14-16):(79-81).
[0010] As a limitation of the present invention, the preparation method of the silanized silica nanotube / ethylene-vinyl acetate film is:
[0011] The silanized silica nanotubes, ethylene-vinyl acetate copolymer, maleic anhydride grafted ethylene-vinyl acetate and antioxidant 1010 are melt-blended at 180-200° C., twin-screw extruded, and calendered at 170-190° C. and 0.2-0.4 MPa to form a silanized silica nanotube / ethylene-vinyl acetate film.
[0012] As a limitation of the present invention, the silanized silica nanotube / ethylene-vinyl acetate film includes, by weight, 10 to 14 parts of silanized silica nanotubes, 43 to 47 parts of ethylene-vinyl acetate copolymer, 2 to 4 parts of maleic anhydride grafted ethylene-vinyl acetate, and 0.16 to 0.20 parts of antioxidant 1010.
[0013] As a limitation of the present invention, the method for preparing the silanized silica nanotubes is:
[0014] Tartaric acid, deionized water and anhydrous ethanol are mixed and stirred to obtain a tartaric acid solution, ethyl orthosilicate is slowly added to the tartaric acid solution, stirred to obtain a tartaric acid solution, and allowed to stand for 10 to 20 minutes, and ammonia water is slowly added, and the mixture is reacted at 20 to 30° C. and 200 to 400 rpm for 25 to 35 minutes. After the reaction is completed, the mixture is allowed to stand for 1 to 3 hours, washed with deionized water, and centrifuged. The separated precipitate is dried at 40 to 60° C. for 1 to 3 hours, and calcined at 480 to 520° C. for 1 to 3 hours to obtain silica nanotubes;
[0015] Mix silica nanotubes and deionized water, and ultrasonically disperse for 10 to 20 minutes to obtain a silica nanotube suspension. Mix KH-550, glacial acetic acid, and deionized water to obtain an acidic silane coupling agent hydrolyzate. Slowly add the acidic silane coupling agent hydrolyzate to the silica nanotube suspension, and react at 75 to 85°C for 1 to 3 hours. After the reaction, wash with deionized water, filter, and dry at 105 to 115°C for 1 to 3 hours to obtain silanized silica nanotubes.
[0016] As a limitation of the present invention, the mass ratio of tartaric acid, tetraethyl orthosilicate and aqueous ammonia is (0.50-0.54):(20.80-20.84):(40.23-40.27).
[0017] As a limitation of the present invention, the mass ratio of the silica nanotubes, KH-550, and glacial acetic acid is (4-6):(0.38-0.42):(0.04-0.06).
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] One-dimensional silica nanotubes with a special ring wall structure were synthesized using tetraethyl orthosilicate as the silicon source and tartaric acid as the template. They not only enhance the mechanical properties of the polymer film, such as impact resistance and tensile strength, but also introduce new energy transfer channels. After being acted upon by force, they can disperse and transmit the force, thus avoiding the damage to the polymer film after stress concentration. By modifying the silica nanotubes with silane coupling agents, more active sites were introduced on the silica nanotubes, which better interacted with the polymer molecular chains, improved the compatibility between the silica nanotubes and the polymer, reduced the occurrence of agglomeration of the silica nanotubes in the polymer matrix, and made the silica nanotubes more evenly dispersed in the polymer.
[0020] After the log board is treated with cage silsesquioxane obtained by hydrolysis and condensation of silane coupling agent and neutral silica sol, many cage silsesquioxane molecules connected to the log board by chemical bonds are deposited on the surface of the log board, which increases the roughness of the board surface and improves the force of the mechanical meshing structure between the log board and the polymer film. The cage structure can capture and entangle the polymer molecular chains, thereby improving the compatibility between the log board and the polymer film, allowing the polymer to penetrate into the micropores on the surface of the log board during the hot pressing process to form a strong nail-like structure, thereby enhancing the bonding strength between the log board and the polymer film and improving the mechanical properties of the film-faced board. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The log board (600mm×300mm×5mm) was provided by Guangxi Zhuangxiang Wood Industry, and the neutral silica sol (1.15~1.17g / cm 3 ) was provided by Shandong Yousuo, and tetraethyl orthosilicate (T819505), antioxidant 1010 (P829612), KH-171 (V823925), and KH-550 (A800523) were provided by Shanghai McLean.
[0023] Embodiment 1: A method for preparing a high-strength wear-resistant film-coated plate, specifically comprising:
[0024] Step 1: Preparation of silica nanotubes
[0025] By mass, 0.52 parts of tartaric acid, 2.60 parts of deionized water and 86.94 parts of anhydrous ethanol were mixed and stirred to obtain a tartaric acid solution, 20.82 parts of ethyl orthosilicate were slowly added to 90.04 parts of the tartaric acid solution, stirred to obtain a tartaric acid solution, and the mixture was allowed to stand for 15 minutes. 40.25 parts of ammonia water were slowly added, and the mixture was reacted at 25°C and 300 rpm for 30 minutes. After the reaction was completed, the mixture was allowed to stand for 2 hours, washed with deionized water, and centrifuged. The separated precipitate was dried at 50°C for 2 hours, and calcined at 500°C for 2 hours to obtain silica nanotubes.
[0026] Step 2: Preparation of silanized silica nanotubes
[0027] By mass, 5 parts of silica nanotubes and 95 parts of deionized water were mixed and ultrasonically dispersed for 15 minutes to obtain a silica nanotube suspension; 0.4 parts of KH-550, 0.05 parts of glacial acetic acid and 19.55 parts of deionized water were mixed to obtain an acidic silane coupling agent hydrolyzate; 20 parts of the acidic silane coupling agent hydrolyzate were slowly added to 100 parts of the silica nanotube suspension, and the mixture was reacted at 80°C for 2 hours. After the reaction was completed, the mixture was washed with deionized water, filtered, and dried at 110°C for 2 hours to obtain silanized silica nanotubes.
[0028] Step 3: Preparation of silanized silica nanotube / ethylene-vinyl acetate film
[0029] By mass, 12 parts of silanized silica nanotubes, 45 parts of ethylene-vinyl acetate copolymer, 3 parts of maleic anhydride grafted ethylene-vinyl acetate, and 0.18 parts of antioxidant 1010 were melt-blended at 190°C, twin-screw extruded, calendered at 180°C and 0.3 MPa, and cooled to obtain a silanized silica nanotube / ethylene-vinyl acetate film.
[0030] Step 4: Preparation of Siloxane-Modified Wood Board
[0031] By mass, 5.0 parts of KH-171, 15 parts of neutral silica sol and 80 parts of ethanol were mixed and stirred to obtain a mixed silicon ethanol solution. The pH of the mixed silicon ethanol solution was adjusted to 12 with sodium hydroxide solution, and the mixture was reacted at 27°C for 3 hours to obtain a cage silsesquioxane solution. The cage silsesquioxane was sprayed onto the surface of the log board, left at 27°C for 24 hours, and cured at 120°C for 2 hours to obtain a siloxane-modified log board.
[0032] Step 5: Prepare high-strength wear-resistant film-coated board
[0033] The siloxane-modified log board was sandwiched between two layers of silanized silica nanotube / ethylene-vinyl acetate film of equal area for hot pressing composite, the hot pressing pressure was 1.0 MPa, the hot pressing time was 20 min, the hot pressing temperature was 140°C, after hot pressing composite, it was cooled to room temperature, pressed again for shaping, the secondary shaping pressure was 1.0 MPa, the secondary shaping time was 5 min, after shaping, it was taken out and trimmed to obtain a high-strength wear-resistant film-coated board.
[0034] Embodiment 2: A method for preparing a high-strength wear-resistant film-coated plate, specifically comprising:
[0035] Step 1: Preparation of silica nanotubes
[0036] By mass, 0.52 parts of tartaric acid, 2.60 parts of deionized water and 86.94 parts of anhydrous ethanol were mixed and stirred to obtain a tartaric acid solution, 20.82 parts of ethyl orthosilicate were slowly added to 90.04 parts of the tartaric acid solution, stirred to obtain a tartaric acid solution, and the mixture was allowed to stand for 15 minutes. 40.25 parts of ammonia water were slowly added, and the mixture was reacted at 25°C and 300 rpm for 30 minutes. After the reaction was completed, the mixture was allowed to stand for 2 hours, washed with deionized water, and centrifuged. The separated precipitate was dried at 50°C for 2 hours, and calcined at 500°C to obtain silica nanotubes.
[0037] Step 2: Preparation of silanized silica nanotubes
[0038] By mass, 5 parts of silica nanotubes and 95 parts of deionized water were mixed and ultrasonically dispersed for 15 minutes to obtain a silica nanotube suspension; 0.4 parts of KH-550, 0.05 parts of glacial acetic acid and 19.55 parts of deionized water were mixed to obtain an acidic silane coupling agent hydrolyzate; 20 parts of the acidic silane coupling agent hydrolyzate were slowly added to 100 parts of the silica nanotube suspension, and the mixture was reacted at 80°C for 2 hours. After the reaction was completed, the mixture was washed with deionized water, filtered, and dried at 110°C for 2 hours to obtain silanized silica nanotubes.
[0039] Step 3: Preparation of silanized silica nanotube / ethylene-vinyl acetate film
[0040] By mass, 10 parts of silanized silica nanotubes, 43 parts of ethylene-vinyl acetate copolymer, 2 parts of maleic anhydride grafted ethylene-vinyl acetate, and 0.16 parts of antioxidant 1010 were melt-blended at 190°C, twin-screw extruded, calendered at 180°C and 0.3 MPa, and cooled to obtain a silanized silica nanotube / ethylene-vinyl acetate film.
[0041] Step 4: Preparation of Siloxane-Modified Wood Board
[0042] By mass, 5.0 parts of KH-171, 15 parts of neutral silica sol and 80 parts of ethanol were mixed and stirred to obtain a mixed silicon ethanol solution. The pH of the mixed silicon ethanol solution was adjusted to 12 with sodium hydroxide solution, and the mixture was reacted at 27°C for 3 hours to obtain a cage silsesquioxane solution. The cage silsesquioxane was sprayed onto the surface of the log board, left at 27°C for 24 hours, and cured at 120°C for 2 hours to obtain a siloxane-modified log board.
[0043] Step 5: Prepare high-strength wear-resistant film-coated board
[0044] The siloxane-modified log board was sandwiched between two layers of silanized silica nanotube / ethylene-vinyl acetate film of equal area for hot pressing composite, the hot pressing pressure was 1.0 MPa, the hot pressing time was 20 min, the hot pressing temperature was 140°C, after hot pressing composite, it was cooled to room temperature, pressed again for shaping, the secondary shaping pressure was 1.0 MPa, the secondary shaping time was 5 min, after shaping, it was taken out and trimmed to obtain a high-strength wear-resistant film-coated board.
[0045] Embodiment 3: A method for preparing a high-strength wear-resistant film-coated plate, specifically comprising:
[0046] Step 1: Preparation of silica nanotubes
[0047] By mass, 0.52 parts of tartaric acid, 2.60 parts of deionized water and 86.94 parts of anhydrous ethanol were mixed and stirred to obtain a tartaric acid solution, 20.82 parts of ethyl orthosilicate were slowly added to 90.04 parts of the tartaric acid solution, stirred to obtain a tartaric acid solution, and the mixture was allowed to stand for 15 minutes. 40.25 parts of ammonia water were slowly added, and the mixture was reacted at 25°C and 300 rpm for 30 minutes. After the reaction was completed, the mixture was allowed to stand for 2 hours, washed with deionized water, and centrifuged. The separated precipitate was dried at 50°C for 2 hours, and calcined at 500°C to obtain silica nanotubes.
[0048] Step 2: Preparation of silanized silica nanotubes
[0049] By mass, 5 parts of silica nanotubes and 95 parts of deionized water were mixed and ultrasonically dispersed for 15 minutes to obtain a silica nanotube suspension; 0.4 parts of KH-550, 0.05 parts of glacial acetic acid and 19.55 parts of deionized water were mixed to obtain an acidic silane coupling agent hydrolyzate; 20 parts of the acidic silane coupling agent hydrolyzate were slowly added to 100 parts of the silica nanotube suspension, and the mixture was reacted at 80°C for 2 hours. After the reaction was completed, the mixture was washed with deionized water, filtered, and dried at 110°C for 2 hours to obtain silanized silica nanotubes.
[0050] Step 3: Preparation of silanized silica nanotube / ethylene-vinyl acetate film
[0051] By mass, 14 parts of silanized silica nanotubes, 47 parts of ethylene-vinyl acetate copolymer, 4 parts of maleic anhydride grafted ethylene-vinyl acetate, and 0.20 parts of antioxidant 1010 were melt-blended at 190°C, twin-screw extruded, calendered at 180°C and 0.3 MPa, and cooled to obtain a silanized silica nanotube / ethylene-vinyl acetate film.
[0052] Step 4: Preparation of Siloxane-Modified Wood Board
[0053] By mass, 5.0 parts of KH-171, 15 parts of neutral silica sol and 80 parts of ethanol were mixed and stirred to obtain a mixed silicon ethanol solution. The pH of the mixed silicon ethanol solution was adjusted to 12 with sodium hydroxide solution, and the mixture was reacted at 27°C for 3 hours to obtain a cage silsesquioxane solution. The cage silsesquioxane was sprayed onto the surface of the log board, left at 27°C for 24 hours, and cured at 120°C for 2 hours to obtain a siloxane-modified log board.
[0054] Step 5: Prepare high-strength wear-resistant film-coated board
[0055] The siloxane-modified log board was sandwiched between two layers of silanized silica nanotube / ethylene-vinyl acetate film of equal area for hot pressing composite, the hot pressing pressure was 1.0 MPa, the hot pressing time was 20 min, the hot pressing temperature was 140°C, after hot pressing composite, it was cooled to room temperature, pressed again for shaping, the secondary shaping pressure was 1.0 MPa, the secondary shaping time was 5 min, after shaping, it was taken out and trimmed to obtain a high-strength wear-resistant film-coated board.
[0056] Based on Example 1, control experiments were carried out, specifically Comparative Example 1, Comparative Example 2 and Comparative Example 3, as described below:
[0057] Comparative Example 1: The silicon dioxide nanotubes were not subjected to silanization treatment, and other conditions were the same as those in Example 1.
[0058] A method for preparing a high-strength wear-resistant film-covered plate, specifically comprising:
[0059] Step 1: Preparation of silica nanotubes
[0060] By mass, 0.52 parts of tartaric acid, 2.60 parts of deionized water and 86.94 parts of anhydrous ethanol were mixed and stirred to obtain a tartaric acid solution, 20.82 parts of ethyl orthosilicate were slowly added to 90.04 parts of the tartaric acid solution, stirred to obtain a tartaric acid solution, and the mixture was allowed to stand for 15 minutes. 40.25 parts of ammonia water were slowly added, and the mixture was reacted at 25°C and 300 rpm for 30 minutes. After the reaction was completed, the mixture was allowed to stand for 2 hours, washed with deionized water, and centrifuged. The separated precipitate was dried at 50°C for 2 hours, and calcined at 500°C for 2 hours to obtain silica nanotubes.
[0061] Step 2: Preparation of silica nanotube / ethylene-vinyl acetate film
[0062] By mass, 12 parts of silica nanotubes, 45 parts of ethylene-vinyl acetate copolymer, 3 parts of maleic anhydride grafted ethylene-vinyl acetate, and 0.18 parts of antioxidant 1010 were melt-blended at 190°C, twin-screw extruded, calendered at 180°C and 0.3 MPa, and cooled to obtain a silica nanotube / ethylene-vinyl acetate film.
[0063] Step 3: Preparation of Siloxane-Modified Wood Board
[0064] By mass, 5.0 parts of KH-171, 15 parts of neutral silica sol and 80 parts of ethanol were mixed and stirred to obtain a mixed silicon ethanol solution. The pH of the mixed silicon ethanol solution was adjusted to 12 with sodium hydroxide solution, and the mixture was reacted at 27°C for 3 hours to obtain a cage silsesquioxane solution. The cage silsesquioxane was sprayed onto the surface of the log board, left at 27°C for 24 hours, and cured at 120°C for 2 hours to obtain a siloxane-modified log board.
[0065] Step 4: Prepare high-strength wear-resistant film-coated board
[0066] The siloxane-modified log board was sandwiched between two layers of silica nanotube / ethylene-vinyl acetate film of equal area for hot pressing composite, the hot pressing pressure was 1.0 MPa, the hot pressing time was 20 min, the hot pressing temperature was 140°C, after hot pressing composite, it was cooled to room temperature, pressed again for shaping, the secondary shaping pressure was 1.0 MPa, the secondary shaping time was 5 min, after shaping, it was taken out and trimmed to obtain a high-strength wear-resistant film-coated board.
[0067] Comparative Example 2: Silanized nano-silica was used instead of silanized silica nanotubes, and the other conditions were the same as those in Example 1.
[0068] A method for preparing a high-strength wear-resistant film-covered plate, specifically comprising:
[0069] Step 1: Preparation of silanized nanosilica
[0070] By mass, 5 parts of nano-silica and 95 parts of deionized water were mixed and ultrasonically dispersed for 15 minutes to obtain a nano-silica suspension; 0.4 parts of KH-550, 0.05 parts of glacial acetic acid and 19.55 parts of deionized water were mixed to obtain an acidic silane coupling agent hydrolyzate; 20 parts of the acidic silane coupling agent hydrolyzate were slowly added to 100 parts of the nano-silica suspension, and the mixture was reacted at 80°C for 2 hours. After the reaction was completed, the mixture was washed with deionized water, filtered, and dried at 110°C for 2 hours to obtain silanized nano-silica.
[0071] Step 2: Preparation of silanized nano-silica / ethylene-vinyl acetate film
[0072] By mass, 12 parts of silanized nano-silica, 45 parts of ethylene-vinyl acetate copolymer, 3 parts of maleic anhydride grafted ethylene-vinyl acetate, and 0.18 parts of antioxidant 1010 were melt-blended at 190°C, twin-screw extruded, calendered at 180°C and 0.3MPa, and cooled to obtain a silanized nano-silica / ethylene-vinyl acetate film.
[0073] Step 3: Preparation of Siloxane-Modified Wood Board
[0074] By mass, 5.0 parts of KH-171, 15 parts of neutral silica sol and 80 parts of ethanol were mixed and stirred to obtain a mixed silicon ethanol solution. The pH of the mixed silicon ethanol solution was adjusted to 12 with sodium hydroxide solution, and the mixture was reacted at 27°C for 3 hours to obtain a cage silsesquioxane solution. The cage silsesquioxane was sprayed onto the surface of the log board, left at 27°C for 24 hours, and cured at 120°C for 2 hours to obtain a siloxane-modified log board.
[0075] Step 4: Prepare high-strength wear-resistant film-coated board
[0076] The siloxane-modified log board was sandwiched between two layers of silanized nano-silica / ethylene-vinyl acetate films of equal area for hot pressing composite. The hot pressing pressure was 1.0 MPa, the hot pressing time was 20 min, and the hot pressing temperature was 140°C. After hot pressing composite, it was cooled to room temperature and pressed again for shaping. The secondary shaping pressure was 1.0 MPa and the secondary shaping time was 5 min. After shaping, it was taken out and trimmed to obtain a high-strength wear-resistant film-coated board.
[0077] Comparative Example 3: No neutral silica sol was added, and other conditions were the same as those in Example 1.
[0078] A method for preparing a high-strength wear-resistant film-covered plate, specifically comprising:
[0079] Step 1: Preparation of silica nanotubes
[0080] By mass, 0.52 parts of tartaric acid, 2.60 parts of deionized water and 86.94 parts of anhydrous ethanol were mixed and stirred to obtain a tartaric acid solution, 20.82 parts of ethyl orthosilicate were slowly added to 90.04 parts of the tartaric acid solution, stirred to obtain a tartaric acid solution, and the mixture was allowed to stand for 15 minutes. 40.25 parts of ammonia water were slowly added, and the mixture was reacted at 25°C and 300 rpm for 30 minutes. After the reaction was completed, the mixture was allowed to stand for 2 hours, washed with deionized water, and centrifuged. The separated precipitate was dried at 50°C for 2 hours, and calcined at 500°C for 2 hours to obtain silica nanotubes.
[0081] Step 2: Preparation of silanized silica nanotubes
[0082] By mass, 5 parts of silica nanotubes and 95 parts of deionized water were mixed and ultrasonically dispersed for 15 minutes to obtain a silica nanotube suspension; 0.4 parts of KH-550, 0.05 parts of glacial acetic acid and 19.55 parts of deionized water were mixed to obtain an acidic silane coupling agent hydrolyzate; 20 parts of the acidic silane coupling agent hydrolyzate were slowly added to 100 parts of the silica nanotube suspension, and the mixture was reacted at 80°C for 2 hours. After the reaction was completed, the mixture was washed with deionized water, filtered, and dried at 110°C for 2 hours to obtain silanized silica nanotubes.
[0083] Step 3: Preparation of silanized silica nanotube / ethylene-vinyl acetate film
[0084] By mass, 12 parts of silanized silica nanotubes, 45 parts of ethylene-vinyl acetate copolymer, 3 parts of maleic anhydride grafted ethylene-vinyl acetate, and 0.18 parts of antioxidant 1010 were melt-blended at 190°C, twin-screw extruded, calendered at 180°C and 0.3 MPa, and cooled to obtain a silanized silica nanotube / ethylene-vinyl acetate film.
[0085] Step 4: Preparation of silane coupling agent modified log board
[0086] By mass, 5.0 parts of KH-171 and 80 parts of ethanol were mixed and stirred to obtain a silane coupling agent solution. The pH of the mixed silane coupling agent solution was adjusted to 12 with a sodium hydroxide solution, and the mixture was reacted at 27°C for 3 hours to obtain an alkaline silane coupling agent solution. The alkaline silane coupling agent solution was sprayed onto the surface of the log board, left at 27°C for 24 hours, and cured at 120°C for 2 hours to obtain a silane coupling agent-modified log board.
[0087] Step 5: Prepare high-strength wear-resistant film-coated board
[0088] The silane coupling agent modified log board was sandwiched between two layers of silanized silica nanotube / ethylene-vinyl acetate film of equal area for hot pressing composite, the hot pressing pressure was 1.0 MPa, the hot pressing time was 20 min, the hot pressing temperature was 140°C, after hot pressing composite, it was cooled to room temperature, pressed again for shaping, the secondary shaping pressure was 1.0 MPa, the secondary shaping time was 5 min, after shaping, it was taken out and trimmed to obtain a high-strength wear-resistant film-coated board.
[0089] Detection experiment:
[0090] The high-strength wear-resistant coated panels required for the test were prepared according to the preparation methods in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively.
[0091] Static bending strength test: According to the "Test Methods for Physical and Chemical Properties of Artificial Boards and Faced Artificial Boards" (GB / T17657-2013), a universal mechanical testing machine was used for testing. Samples were cut from the 6 prepared high-strength wear-resistant coated panels. The sample size was 170mm×50mm×6mm. The samples were placed flat on the supports, and load was applied to the center of the samples at a uniform speed. The maximum load applied when the samples were destroyed was recorded, and the static bending strength of each sample was calculated.
[0092] Surface bonding strength test: According to the Test Methods for Physical and Chemical Properties of Artificial Boards and Faced Artificial Boards (GB / T 17657-2013), a universal mechanical testing machine was used for testing. Samples were cut from the 6 prepared high-strength wear-resistant coated panels. The sample size was 50mm×50mm×6mm. A circular groove with an inner diameter of 37.5mm and a groove depth of 0.3mm was milled out on one side of the sample with a milling cutter. The chuck and the circular surface of the sample were glued together and compacted with epoxy resin glue. The sample was installed on the testing machine, and a load was applied to destroy the sample. The maximum load at the time of destruction was recorded, and the surface bonding strength of each sample was calculated.
[0093] Surface wear resistance test: According to the "Test Methods for Physical and Chemical Properties of Artificial Boards and Faced Artificial Boards" (GB / T 17657-2013), an abrasion testing machine was used for testing. Samples were cut from the 6 prepared high-strength wear-resistant coated panels. The sample size was 100mm×100mm×6mm. The initial weight of each sample was measured and recorded. After the abrasion testing machine was calibrated, the sample was fixed on the fixture and ground with a grinding wheel. The grinding pressure was 5.0N and the grinding speed was 500r. After grinding, the specimen was removed to remove the dust on the surface. The mass of the sample after grinding was measured and the wear value of the sample was calculated.
[0094]
[0095] Conclusion: It can be seen from the experiment that the high-strength wear-resistant film-faced panels prepared by the preparation method of Example 1 are superior to the high-strength wear-resistant film-faced panels prepared by the preparation methods of Comparative Examples 1, 2 and 3 in static bending strength test, surface bonding strength test and surface wear resistance test, effectively solving the problem of insufficient static bending strength and wear resistance of the film-faced panels for construction.
[0096] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a high-strength wear-resistant film-faced plate, characterized in that: The preparation method is: The siloxane-modified log board is sandwiched between two layers of silanized silica nanotube / ethylene-vinyl acetate film for hot pressing and compounding. The hot pressing pressure is 0.8-1.2 MPa, the hot pressing time is 15-25 min, and the hot pressing temperature is 130-150°C. After hot pressing and compounding, it is cooled to room temperature and pressed again for shaping. The secondary shaping pressure is 0.8-1.2 MPa and the secondary shaping time is 3-8 min. After shaping, it is taken out and trimmed to obtain a high-strength wear-resistant coated board.
2. The method for preparing a high-strength wear-resistant film-faced plate according to claim 1, characterized in that: The preparation method of siloxane modified log board is as follows: Mix KH-171, neutral silica sol and ethanol, stir evenly to obtain a mixed silica ethanol solution, adjust the pH of the mixed silica ethanol solution to alkaline, react at 25-30°C for 2-4 hours to obtain a cage silsesquioxane solution, spray the cage silsesquioxane solution onto the surface of the log board, let it stand at 25-30°C for 20-28 hours, and cure it at 110-130°C for 1-3 hours to obtain a siloxane-modified log board.
3. The method for preparing a high-strength wear-resistant film-faced plate according to claim 2, characterized in that: The mass ratio of KH-171, neutral silica sol and ethanol is (4.9-5.1):(14-16):(79-81).
4. The method for preparing a high-strength wear-resistant film-faced plate according to claim 1, characterized in that: The preparation method of silanized silica nanotube / ethylene-vinyl acetate film is as follows: The silanized silica nanotubes, ethylene-vinyl acetate copolymer, maleic anhydride grafted ethylene-vinyl acetate and antioxidant 1010 are melt-blended at 180-200° C., twin-screw extruded, and calendered at 170-190° C. and 0.2-0.4 MPa to form a silanized silica nanotube / ethylene-vinyl acetate film.
5. The method for preparing a high-strength wear-resistant film-faced plate according to claim 4, characterized in that: The silanized silica nanotube / ethylene-vinyl acetate film comprises 10 to 14 parts of silanized silica nanotubes, 43 to 47 parts of ethylene-vinyl acetate copolymer, 2 to 4 parts of maleic anhydride grafted ethylene-vinyl acetate, and 0.16 to 0.20 parts of antioxidant 1010, based on mass.
6. The method for preparing a high-strength wear-resistant film-faced plate according to claim 4, characterized in that: The preparation method of silanized silica nanotubes is as follows: Tartaric acid, deionized water and anhydrous ethanol are mixed and stirred to obtain a tartaric acid solution, ethyl orthosilicate is slowly added to the tartaric acid solution, stirred to obtain a tartaric acid solution, and allowed to stand for 10 to 20 minutes, and ammonia water is slowly added, and the mixture is reacted at 20 to 30° C. and 200 to 400 rpm for 25 to 35 minutes. After the reaction is completed, the mixture is allowed to stand for 1 to 3 hours, washed with deionized water, and centrifuged. The separated precipitate is dried at 40 to 60° C. for 1 to 3 hours, and calcined at 480 to 520° C. for 1 to 3 hours to obtain silica nanotubes; Mix silica nanotubes and deionized water, and ultrasonically disperse for 10 to 20 minutes to obtain a silica nanotube suspension. Mix KH-550, glacial acetic acid, and deionized water to obtain an acidic silane coupling agent hydrolyzate. Slowly add the acidic silane coupling agent hydrolyzate to the silica nanotube suspension, and react at 75 to 85°C for 1 to 3 hours. After the reaction, wash with deionized water, filter, and dry at 105 to 115°C for 1 to 3 hours to obtain silanized silica nanotubes.
7. The method for preparing a high-strength wear-resistant film-faced plate according to claim 6, characterized in that: The mass ratio of tartaric acid, tetraethyl orthosilicate and aqueous ammonia is (0.50-0.54):(20.80-20.84):(40.23-40.27).
8. The method for preparing a high-strength wear-resistant film-faced plate according to claim 6, characterized in that: The mass ratio of silica nanotubes, KH-550 and glacial acetic acid is (4-6):(0.38-0.42):(0.04-0.06).
Citation Information
Patent Citations
Silicon rubber composite material and method for improving electric insulation performance
CN102585511A
Wear-resistant decoration wood sheet and processing method thereof and composite board manufactured by using wear-resistant decoration wood sheet
CN102837468A
Ozone wear-resisting environment-friendly ecological board and production process thereof
CN106182217A
Preparation method of abrasion-resistant veneer
CN108081404A
Low-temperature toughened and modified nylon 6 composite material and preparation method thereof
CN117343535A
Cited By
Bamboo-wood composite shaving board and preparation method thereof
CN120439414A